Combination of monopolar 2 MHz radiofrequency and electrical multidirectional stimulation for reducing abdominal circumference and enhancing the muscle definition in subjects with overweight range body mass index - Manuskiatti W. (2023)
Background: The popularity of noninvasive body contouring procedures has been steadily increasing in recent years, however, studies evaluating its effectiveness in individuals with overweight range body mass index (BMI) are limited. Objective: To evaluate the efficacy and safety of combined 2 MHz radiofrequency (RF) and electrical multidirectional stimulation (EMDS) for the improvement of the abdominal contour in subjects with overweight range BMI. Methods: Twelve participants with overweight range BMI (23.6–24.9 kg/m2) underwent a single RF treatment, followed by a series of six EMDS treatments. Follow-up assessments (abdominal circumference [AC] and skinfold thickness measurements) were scheduled 1, 2, and 3 months after the final session. Results: At 1 month after the final treatment, a 3.1% (2.6 ± 0.47 cm, mean ± SD) significant reduction in mean AC was observed (p ˂ 0.001) and a maximal skinfold thickness reduction of 14% (4.6 ± 1.1 mm) was also noted (p = 0.032). Transient dysesthesia lasting 2–3 hours after EMDS treatment was the most common adverse effect reported by 5 of 12 subjects (41.7%), with no other serious side effects. Conclusions: Combined RF and EMDS treatments are safe and effective, yielding significant reductions in both AC and skinfold thickness in patients with overweight range BMI, causing only minimal and transient adverse effects.